A funny kind of paradise - Owens, Jo, 1961- (Random House Canada, 2021)
"When her husband left her with a baby, a toddler and a fledgling business, Francesca managed - she wasn't always gentle or patient, but the business thrived and Chris and Angelina had food to eat. At nearly 70, she feels she's earned a peaceful retirement. But when a massive stroke leaves her voiceless, partially paralysed and wholly reliant on the staff of an extended care facility, it seems her freedom is lost."--Provided by publisher.